Professional Activity Of The Leader Methodology For Improving The Social-Psychological Characteristics Of Development - Sherzod Shadiyev Fayzullayevich (Euro Asian Journal Publishing, 2024)
In the article, the specifics of improving the socio-psychological characteristics of the development of the professional activity of the leader, personal qualities of the leader,spiritual image, qualifications and skills acquired in work activities, humanitarian qualities of a high level in education activities, loyalty to his work, discipline, humanity, morality qualities, educational content, its form, methods, purposeful development also, the psychological, pedagogical, methodological, didactic and methodological possibilities for improving the socio-psychological characteristics of the development of the professional activity of the leader and resources based on the mechanism of its introduction into practice are described
Keywords: leader; professional activity; management